The second species of Cyanocypus He & Zhou (Coleoptera: Staphylinidae: Staphylininae) with remarks on the systematic position of the genus - Hu, Fang-Shuo; Solodovnikov, Alexey (Zootaxa, 2026)
We describe a second species in the hitherto monotypic genus Cyanocypus He & Zhou, C. aeneus sp. nov. and examined additional specimens of C. leukos He & Zhou, all material coming from northern Vietnam. These additions allow to improve the diagnosis of Cyanocypus, extend the known distribution of this genus and C. leukos to northern Vietnam and further discuss synapomorphic characters of the Ocypus-group of genera. We provide illustrations of both C. aeneus sp. nov. and C. leukos.